Research methods in radiology : a practical guide - Doria, Andrea S.; Tomlinson, George (George A.); Beyene, Joseph; Moineddin, Rahim; Meaney, Christopher; Shaikh, Mateen (New York : Thieme Publishers, 2018)
Research Methods in Radiology provides concise, practical insights on how to design clinical and experimental studies in diagnostic imaging. This unique resource encompasses contributions from leaders in academic radiology as well as top epidemiologists, biostatisticians, and librarians with vast multidisciplinary and radiology research experience. The material reflects years of expertise teaching core biostatistics in radiology principles to residents, fellows, radiologists, and epidemiologists. Given the vast amount of published information on research methodology and statistics in radiology.
Overview of research designs applied to radiology / Andreas Roposch and Andrea S. Doria -- Descriptive statistics / Mateen Shaikh and Hadas Moshonov -- Statistical methods for analysis of diagnostic tests / George Tomlinson, Gerald Lebovic, Connie Marras, and Andrea S. Doria -- Measurement : validity, reliability, responsiveness / Alexandra M. Easson, George Tomlinson, and Andrea S. Doria -- Observational designs / Marinka Twilt, Ivan R. Diamond, and Susanne M. Benseler -- Randomized controlled trials / Ivan R. Diamond and Brian M. Feldman -- Systemic reviews, evidence-based imaging, and knowledge translation / Andrea S. Doria, Jennifer Stinson, and Prakeshkumar Shah -- Decision analysis / Ava A. John-Baptiste and Sapna Rawal -- Costs and consequences : an introduction to economic evaluation in radiology / Wendy J. Ungar and Richard Zur -- Conducting and publishing research / Andrea S. Doria, Peter Strouse, and Thomasin Adams-Webber -- Obtaining ethics approval, data management, and budget formulation / Ravi Menezes, Tuula Kalliomäki, and Yasser Karimzad -- Steps for using research as a success tool in academia / Aine Kelly and Suresh Mukherji -- Introduction to statistical inference : point estimation, confidence intervals, and hypothesis tests / Christopher Meaney, Rahim Moineddin, and George Tomlinson -- An introduction to linear and logistic regression / Christopher Meaney, Mateen Sheik, Rahim Moineddin, and Andrea S. Doria -- Sample size estimation / Mateen Shaikh, Joseph Beyene, and Andrea S. Doria -- Introduction to meta-analysis / Joseph Beyene, Binod Neupane, and Zelalem Firisa.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 650
Keywords: Radiography -- methods; Biomedical Research -- methods; Research Design; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Radiography; Electronic books; Electronic books